Macrophages and fibroblasts during inflammation and tissue repair in models of organ regeneration. Issue 2 (6th June 2017) - Mescher, Anthony L.
Abstract: This review provides a concise summary of the changing phenotypes of macrophages and fibroblastic cells during the local inflammatory response, the onset of tissue repair, and the resolution of inflammation which follow injury to an organ. Both cell populations respond directly to damage and present coordinated sequences of activation states which determine the reparative outcome, ranging from true regeneration of the organ to fibrosis and variable functional deficits. Recent work with mammalian models of organ regeneration, including regeneration of full‐thickness skin, hair follicles, ear punch tissues, and digit tips, is summarized and the roles of local immune cells in these systems are discussed. New investigations of the early phase of amphibian limb and tail regeneration, including the effects of pro‐inflammatory and anti‐inflammatory agents, are then briefly discussed, focusing on the transition from the normally covert inflammatory response to the initiation of the regeneration blastema by migrating fibroblasts and the expression of genes for limb patterning.